Kebijakan Pembagian Hasil Pengelolaan Objek Wisata di Kabupaten Bangli - Luh Putu Suryani; Ni Made Puspasutari Ujianti; Ida Ayu Putu Widiati (Fakultas Hukum, Universitas Warmadewa, 2022)
The island of Bali is famous for its natural beauty. Likewise with Bangli Regency which is one of the regencies on the island of Bali which is famous for having water tourism destinations that are no less beautiful than other places on the island of Bali. Tibumana Waterfall is a tourist attraction managed by the traditional village through an agreement made between the traditional village and the Apuan village government through an agreement. On the basis of the agreement, the traditional village can better manage tourist objects and attractions, beautiful in accordance with the Hindu order, so that their uniqueness and beauty can be maintained and developed. The cooperation agreement between the Bendesa Adat Bangunlemah Kawan and the Perbekel of Apuan Village is in accordance with the anatomy of the contract which requires that the contract must include the scope, rights and obligations, provisions for force majeure and provisions for dispute resolution. The policy model in the distribution of the results of the management of tourism objects in the Tibumana waterfall does not reflect the principle of justice. To be more ideal, before the contract is drawn up, the Village Government forms a Village Regulation which regulates the management of tourism objects in the Apuan village area, because the opening of tourist objects to tourists will of course have a levy to be paid. For illegal levies, the retribution must go through a Village Regulation. After the village regulations are formed, contracts are drawn up to determine more concrete matters.